Differences in Swim Bladder Histology of Anguilla bicolor bicolor at Various Stages of Sexual Maturity - Nur Indah Septriani; Muhammad Ardillah Rusydan; Gizela Aulia Agustin; Nareta Defiani; Fajar Sofyantoro; Ariel Hananya; Dwi Eny Djoko Setyono (Universitas Gadjah Mada, 2023)
The current study observed the histological differences of the swim bladder of the tropical eel, Anguilla bicolor bicolor, as an adaptation resulting from hydrostatic change. A total of 15 eels were collected from Pasir Puncu, Keburuhan, Purworejo and Segara Anakan, Cilacap, Indonesia in June 2017, September 2020, and April 2021. The eels were grouped into 4 stages based on the silvering stage and sex, namely: yellow undifferentiated, yellow female, silver male, and silver female. The average length and body weight of yellow undifferentiated eels were 255.07 ± 45.91 mm and 13.66 ± 8.5 g, respectively; for yellow female, the values were 374.35 ± 41.51 mm and 56.5 ± 12.02 g; for silver male, the values were 432.43 ± 15.15 mm and 140.29 ± 13.85 g; and for silver female were 702 ± 0.00 mm and 545 ± 11.31 g. The present study successfully recorded the histological structure of the swim bladder of A. bicolor bicolor in silver male and silver female stages. Silver males and females displayed a greater significant development of the swim bladder than yellow stages in the gas gland, mucosa, and submucosa layers. These results suggest that an increase in the gas gland thickness allows a greater contribution from gas to gas secretion, the mucosa exerts a mechanical effect on the newly formed gas bubbles, and the submucosa thickness reduces gas conductivity from the swim bladder wall.